Reactivity of histidine and lysine side-chains with diethylpyrocarbonate -- a method to identify surface exposed residues in proteins - Hnízda, Ales; Santrůcek, Jirí; Sanda, Miloslav; Strohalm, Martin; Kodícek, Milan (Journal of biochemical and biophysical methods, 2008)
The chemical modification of amino acid side-chains followed by mass spectrometric detection can reveal at least partial information about the 3-D structure of proteins. In this work we tested diethylpyrocarbonate, as a common histidyl modification agent, for this purpose. Appropriate conditions for the reaction and detection of modified amino acids were developed using angiotensin II as a model peptide. We studied the modification of several model proteins with a known spatial arrangement (insulin, cytochrome c, lysozyme and human serum albumin). Our results revealed that the surface accessibility of residues is a necessary, although in itself insufficient, condition for their reactivity; the microenvironment of side-chains and the dynamics of protein structure also affect the ability of residues to react. However the detection of modified residues can be taken as proof of their surface accessibility, and of direct contact with solvent molecules.
Keywords: kur domácí; diethylpyrokarbonát; povrchové vlastnosti; proteiny; Diethyl Pyrocarbonate; Chickens; molekulární struktura; Molecular Structure; Lysine; lysin; Animals; lidé; Humans; zvířata; Surface Properties; koně; spektrofotometrie; Spectrophotometry; Histidine; Proteins; Horses; histidin